Silylboranes as Powerful Tools in Organic Synthesis: Stereo- and Regioselective Reactions with 1,n-Enynes - Moberg, Christina (Synthesis, 2020)
Bismetalated alkenes, accessible by element–element addition to alkynes, are valuable building blocks in organic synthesis, providing wide opportunities for divergent synthesis. Silaboration of alkynes with a pendant olefinic group, catalyzed by group 10 metal complexes, and subsequent transformation of the silicon and boron functional groups give access to densely functionalized 1,3-dienes and 1,3,5-trienes with defined stereo- and regiochemistry, 1,2-dienes, and carbocyclic and heterocyclic products.1 Introduction2 Background3 Reactions with 1,3-Enynes4 Cyclization 1,6-Enynes5 Cyclization 1,7-Enynes6 Cyclization of 1,n-Enynes (n > 7)7 Cyclization of Dienynes and Enediynes8 Cyclization of 1,6-Diynes9 Conclusions
Keywords: cyclization; diene; enyne; silaboration; triene